Emergence of Socially Assistive Robotics in Rehabilitation for Children with Cerebral Palsy: A Review. (20th June 2016) - Malik, Norjasween Abdul; Hanapiah, Fazah Akhtar; Rahman, Rabiatul Adawiah Abdul; Yussof, Hanafiah
Robotic assistive technology is today widely used in rehabilitation. Social assistive robotics (SAR) is one of the developing areas of research with potential advantages for areas involving elderly care, people with cognitive impairment, rehabilitation for people with physical disabilities and for educational purposes. Cerebral palsy (CP) is a common neurological disorder among children that impairs motor function and may involve cognitive function. The use of social assistive robotic technology serves as a potential approach for CP rehabilitation. The objective of this paper is to review published articles regarding SAR in rehabilitation for children with CP. Twelve published studies have been identified and will be discussed in this review paper.